Pembuatan Jadam Liquid Fertilizer sebagai Solusi Peningkatan Kesuburan Tanah di Desa Antutan (International Forum of Researchers and Lecturers, 2025)
Antutan Village faces soil fertility problems due to high acidity caused by the intensive use of chemical fertilizers without being balanced with organic matter. This has resulted in low agricultural productivity, especially in rice and cocoa crops. As an alternative solution that is environmentally friendly and economical, Jadam Liquid Fertilizer (JLF) was introduced to farmers through socialization and demonstration activities. This activity aims to increase farmers' understanding of the benefits of organic fertilizer in improving soil fertility and provide skills in the manufacture and application of JLF independently. The method used in this activity includes the delivery of material on the negative impact of excessive use of chemical fertilizers, the importance of microorganisms in the soil, and the technique of making JLF using local materials such as weeds, rice straw, and banana stump. Live demonstrations were conducted to show the fermentation process as well as how to apply JLF on farmland. Farmers were given the opportunity to actively participate in every stage of JLF production and application.The results showed a positive response from farmers who were interested in adopting this technology as an alternative to organic fertilizer. With this socialization and demonstration, it is expected that farmers can reduce dependence on chemical fertilizers and improve soil fertility in a sustainable manner. The application of JLF is expected to be the first step in the development of sustainable agriculture in Antutan Village.